Determining Factors of Cloud Computing Adoption: A Study of Indonesian Local Government Employees - Nur Restu Amalia Salam; Syaiful Ali (Journal of Accounting and Investment, 2020)
Research aims: This study aims to identify the factors that influence the Indonesian local government employees to adopt cloud computing.Design/Methodology/Approach: A Unified Theory of Acceptance and Use of Technology (UTAUT) theory were employed to identify these factors. Research data were obtained using an online survey of employees, working in local governments in Indonesia. This study obtained 123 responses, which were then processed utilizing the structural equation modeling approach.Research findings: The results showed that Performance Expectations, Business Expectations, and Perception of Availability had a positive effect on the intention of local government employees to use cloud computing.Theoretical contribution/ Originality: This study expanded the UTAUT model by including security factors. Thus, creating a new cloud computing adoption model contributed to a theoretical finding in the context of government cloud computing adoption.Practitioner/Policy implication: The results of this study make practical contributions to cloud computing service providers in order to understand what factors drive the adoption of cloud computing by local government employees. In addition, the study also helps the top management in local government organizations to develop adoption strategies by understanding the influential determinants of cloud computing adoption on their employees.Research limitation/Implication: The context of this study is restricted to Indonesian local government employees. The local government employees have their characteristics, and it is different from other government employees in the central government.